PERAN PENYESUAIAN DIRI SEBAGAI MEDIATOR DARI PENGARUH RELIGIUSITAS TERHADAP KEBAHAGIAAN SANTRI PONDOK PESANTREN - Mutiara Subhiyah; Fuad Nashori (Department of Islamic Psychology, The State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, Indonesia, 2021)
This study aimed to observe to what extent the self-adaptation has a role as mediator in the correlation of religiosity and happiness. It involved 204 new santri in Islamic Boarding School X in Bekasi. This study used the scale of Oxford Happiness Questionnaire (OHQ) as developed by Hills and Argyle, Indonesian Psychological Measurement of Islamic Religiousness (I-PMIR) developed by Abu-Raiya, et al. adapted into Indonesia Language by Salsabila, et al. and student Adaptation to College Questionnaire (SACQ) by Baker and Siryk. Data were analized using exploratory factor analysis by means of software SPSS 20 and PROCESS macro analysis through SPSS 20 software. The results of this study showed that religiosity positively affecting self-adaptation and happiness, and self-adaptation mediated the effects of religiosity on happiness. Thus, the hypothesis in this study was accepted.